Cyclic ammonium grafted poly (arylene ether ketone) hydroxide ion exchange membranes for alkaline water electrolysis with high chemical stability and cell efficiency. (1st May 2018) - Lee, Nakwon; Duong, Diem Tham; Kim, Dukjoon
Abstract: Poly (arylene ether) ketone possessing 1-(3-aminopropyl)-4-methylpiperazine group at pendant site (PAEK-APMP) was synthesized for anion exchange membrane (AEM) in alkaline water electrolysis, and its chemical structure was confirmed by 1 H NMR spectroscopy. A variety of physical properties of membranes for electrolysis were examined including water uptake, ion conductivity, and tensile strength and elongation, and those are correlated with the ion cluster dimension measured by SAXS. In order to confirm its long term durability, the chemical and hydrolytic stability were also tested. Among a series of the synthesized membranes, PAEK-APMP75 and PAEK-APMP100 exhibited excellent hydroxide ion conductivity (>0.011 S cm -1  at 60 °C) under low water uptake (<55% at 60 °C). PAEK-APMP75 and PAEK-APMP 100 membranes showed superior properties to the commercial Fumasep FAA-3 and the PAEK membrane grafted with the quaternary ammonium (QA) groups, PAEK-QA, in wide aspects - thermal, mechanical, chemical and hydrolytic stability. From the electrolytic cell test, PAEK-APMP membranes showed better performance and durability than Fumasep FAA-3 and PAEK-QA membranes, confirming that it is quite a suitable for industrial application for water electrolysis.